Dinamika Persaingan Ritel Modern: Analisis Game Theory pada Alfamart dan Indomaret (Kajian Literatur) - Rexy Andalangi Maatuil; Eklesiania Pongulu; Jerlita Utubira; Syalom. T. Arikalang; Adis Omaleng (Indonesia Economic Journal, 2025)
This study aims to analyze the dynamics of modern retail competition between Alfamart and Indomaret using game theory. The type of research employed is a literature study approach; this study does not conduct field data collection but relies on critical analysis of academic literature to formulate the competitive patterns of Alfamart–Indomaret within the framework of game theory. The findings indicate that in the dynamics of modern retail competition, the SLR results show that the rivalry between Alfamart and Indomaret constitutes a highly intense form of duopolistic competition, characterized by massive business expansion strategies and rapid responses to changes in competitors’ strategies. The study also identifies that service differentiation strategies are an important element in this competitive dynamic. Both Alfamart and Indomaret strive to expand additional services such as bill payments, top-ups, and other digital services to broaden the function of their outlets as daily transaction centers. This indicates that competition is no longer limited to retail product sales but has evolved toward digital ecosystem–based services. The study further finds that location-based competition between the two players exhibits a pattern of mutual imitation, where the decision to open a new store by one party is almost always followed by its competitor within a relatively close radius. This pattern reinforces the interdependent relationship that characterizes a duopoly.